BS EN 61156-7. Multicore and symmetrical pair/quad cables for digital communications. Part 7. Symmetrical pair cables with transmission characteristics up to 1 200 MHz. Sectional specification for digital and analog communication cables (28th September 2021) - British Standards Institution,
No abstract available